IMPLEMENTASI PENGUMPULAN DAN ANALISIS DATA BERBASIS KEBUTUHAN DALAM PERENCANAAN PENDIDIKAN: STUDI KASUS DI SD ISLAM TERPADU AN-NUR - Muhammad Fitriadi; Nazarni Dara Puteri; Rahma, Raihani; Suhaimi; Sulistiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of data in educational planning is crucial in ensuring that school policies are based on real needs. However, in practice, some educational units still do not have an integrated data collection and analysis system in the planning process. This study aims to describe the implementation of data collection and analysis in the educational planning process at SD Islam Terpadu An-Nur, Tapin, South Kalimantan. The study used a qualitative approach with a case study design, through interviews, observations, and document analysis relevant to the research focus. The results show that SDIT An-Nur has developed a data collection system that covers academic, non-academic, community, and institutional aspects, analyzed through a combination of descriptive analysis, gap analysis, and collective deliberation in school forums. This process allows schools to identify needs more comprehensively and translate them into planning policies, including in the preparation of the RKAS (Regional Work Plan and Budget). This study proposes the Needs-Based Planning and Community Collaboration Model (MPBKK) as a conceptual contribution to educational planning practices in schools. These findings indicate that the systematic integration of data collection and analysis can strengthen the practice of needs-based educational planning in schools.